2020
DOI: 10.1021/acs.cgd.0c00316
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Resilience of GaN Nanowires, Crested and Surficially Passivated by AlN

Abstract: The rapidly increasing interest in nanowires (NWs) of GaN and associated III-Nitrides for (opto-)­electronic applications demands immediate address of the technological challenges associated with NW-based device processing. Toward this end, we demonstrate in this work an approach to suppress the thermal decomposition of GaN NWs, which also serves to passivate the surface states. Both of these effects are known to be significant challenges in the development of GaN-NW-based devices. The approach entails AlN cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The length and diameter of the AlN-capped GaN NWs of sample I are the same as those of the as-grown NWs of this sample (550 and 56 nm, respectively). This confirms that the AlN-cap protects the underlying GaN NWs from thermal decomposition, as demonstrated in our earlier work …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The length and diameter of the AlN-capped GaN NWs of sample I are the same as those of the as-grown NWs of this sample (550 and 56 nm, respectively). This confirms that the AlN-cap protects the underlying GaN NWs from thermal decomposition, as demonstrated in our earlier work …”
Section: Resultssupporting
confidence: 90%
“…The distinct strategy developed for realization of the GaN NWQDs by MBE is schematically shown in Figure . Thermal decomposition of GaN NWs at high temperatures (either during growth or during postgrowth thermal annealing) is now well-established. , In a previous report, we have shown that this decomposition can be completely suppressed by cresting the as-grown GaN NWs with a thin AlN cap layer . Combining this capability with controlled decomposition of GaN NWs is the crucial enabling step of the NWQD formation technique, demonstrated here.…”
Section: Experimental Methodsmentioning
confidence: 63%
See 2 more Smart Citations
“…III-Nitride materials for optoelectronic applications have gained unprecedented interest around the globe due to their bandgap tuning ability, spanning from deep UV to near-infrared region. InGaN-based green light emitting diodes (LEDs) and laser diodes (LDs) with high efficiency are of particular importance due to their vast relevance in display applications, undersea submarine communication, pico-projectors, medical surgery, etc. Despite relentless efforts by various research groups, poor efficiency remains a major issue to look into with indium incorporation crossing 20% (peak emission wavelength λ p ≥ 500 nm). This imminent setback comes to play mainly because of the non-radiative defects, owing to high lattice mismatch and adverse growth conditions to incorporate high indium composition. Defects in the active region play an important role in determining the performance of these optical devices by opening a non-radiative channel for injected carriers in the QWs. Here, we demonstrate that all the defect states in the active region do not necessarily participate in the non-radiative recombination process. Instead, they can be saturated with carriers at high injection.…”
mentioning
confidence: 99%